1979
DOI: 10.1002/iroh.19790640417
|View full text |Cite
|
Sign up to set email alerts
|

Algological Investigations in the Polluted Ashar Canal and Shatt al‐Arab in Basrah (Iraq)

Abstract: In the Ashar Canal in the city of Basrah and in the Shatt al‐Arab directly below the mouth of the Ashar Canal algological and saprobiological investigations were carried out. The water of the Ashar Canal is β‐ to α‐mesosaprobic, the water of the Shatt al‐Arab below the mouth of the Ashar Canal is β‐mesosaprobic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Taxonomic implications. The striae per 10 lm of P. laevis reported in previous studies ranges from 12 to 18 in 10 lm (e.g., Bourrelly and Manguin 1952, Al-Saadi et al 1979, Fr ankov a-Koz akov a et al 2007, Cavalcante et al 2013, Mamanazarova and Gololobova 2017, Park et al 2017, with an exceptional case in that P. laevis found in Iran had 9-12/ 10 lm (Sharifinia et al 2016). The striae densities in most of the valves observed in this study, from 13 to 19, fit well within this range.…”
Section: Discussionsupporting
confidence: 85%
“…Taxonomic implications. The striae per 10 lm of P. laevis reported in previous studies ranges from 12 to 18 in 10 lm (e.g., Bourrelly and Manguin 1952, Al-Saadi et al 1979, Fr ankov a-Koz akov a et al 2007, Cavalcante et al 2013, Mamanazarova and Gololobova 2017, Park et al 2017, with an exceptional case in that P. laevis found in Iran had 9-12/ 10 lm (Sharifinia et al 2016). The striae densities in most of the valves observed in this study, from 13 to 19, fit well within this range.…”
Section: Discussionsupporting
confidence: 85%
“…The chlorosity in the canal was much higher than in the estuary in both months . Al-Saadi et al (1979a), Sarker et al (1980) and Antoine & Al-Saadi (1982) also reported such results in the canal and the estuary . Domestic sewage disposal into the canal markedly increases its chloride content .…”
Section: Environmental Variablesmentioning
confidence: 62%
“…Al-Saadi et al (1979a) and Antoine & Al-Saadi (1982) also recorded higher transparency in the estuary than in the canal . Turbidity in the canal is mainly related to the high algal population (Antoine & Al-Saadi 1982) as well as to sewage disposal .…”
Section: Environmental Variablesmentioning
confidence: 99%
“…The importance of benthic algae in Iraqi aquatic ecosystems was subjected to investigations recently [1]- [4]. Many authors have previously recognized benthic algae as bioindicators in different aquatic ecosystems of Iraq [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of diatomic algae was also observed in different studies. The abundance of some diatomic species may reflect the status of the aquatic ecosystem such as the trophic status [11] or extent of organic pollution [1] [5] and to water quality [3]. Many authors have pointed out the abundance of diatoms and explained that the diatomic algae had the ability to alter the conditions of their environment, but their community structure responded to altered physicochemical and biological variables in the ecosystem [12]- [14].…”
Section: Introductionmentioning
confidence: 99%